Story structure and reading comprehension in the hearing-impaired - Suma Narasimhan (Journal of All India Institute of Speech and Hearing, 1970)
The aim of this dissertation is to find the effect of story structure change on reading comprehension in normals and hearing-impaired. So as to accomplish this, thirtysix subjects (18 normals and 18 hearing impaired) were taken for the study. They are of the ages 8-9, 9-10 and 10-11 years. The degree of the hearing loss ranged from moderately severe to profound SN loss. Four stories were selected from the stories prepared by Rama (1980). These are considered as the original stories. The revised versions of these are the stories with the change of sentence structure.